Proteinase và hoạt độ ức chế proteinase của một số cây thuốc chữa bệnh mụn nhọt - mẩn ngứa - lở loét - bệnh da - Phạm, Thị Trân Châu (2016)
Proteinases and Proteinase Inhibitory Activity of Some Medicinal Plants used for Treatment of Boils - Pruritus Impetigo- Skin Diseases An investigation of sixty two sample extracts derived from 57 medicinal plants used for treatment of boils, pruritus, impetigo and skin diseases has shown that: 32 of the samples possess proteolytic activity (PA), but only 5 of them are of high PA, namely Glycosmis citrifolia, Cassia hirsuta, Euphorbia tithymaloides, Ageratum conizoides, Rhinacanthus nasutus. Seventeen of the samples have exhibited both trypsin inhibitory activity (TIA) and chymotrypsin inhibitory activity (ChIA) in the range of 38 to over 6000 mIU/gram, most of them have shown ChIA which is from 1.5 to 2 times higher than TIA. Among these, five samples have shown inhibitory activity against proteinases isolated from Pseudomonas aeruginosa, they are: Sageretia theezans, Zanthoxylum avicennae, Rheum officinale, Syzygium sp., Syzygium resinosum. The last one is richest in proteinase inhibitors, showing at least 3 TI / ChI bands, 4 PA bands on polyacrylamide gel electrophoregram and also inhibits the growth of Staphylococcus aureus.